Designing a constructivist learning aid module in disentangling least mastered competencies in the wave motion - Soltura, Russel T. (Journal of Research in Instructional, 2022)
This study sought to design constructivist learning aid module in disentangling least mastered competencies in wave motion among the 72 Grade 7 students of Quezon Science High School, S.Y. 2019-2020. Specifically, it sought to test if there is significant difference between the pre-test and post-test scores. Also, level of acceptability of the developed instructional material was evaluated. A 30-item achievement test (pre-test and post-test) and the questionnaire. One-group pre-test post-test design was used as the research design. The findings showed that the mean scores of the students in the pre-test and post-test is 11.29 and 29.08 respectively. The computed t-value is -13.176 is less than the tabular value of -1.99 at 0.05 level of significance. There is a significant difference between the pre-test and post-test scores after the utilization of the said learning material. It implies that the constructivist learning aid module is a valid tool in disentangling the least mastered competencies in wave motion. The average weighted mean values for the following criteria on the level of acceptability are as follows: learning objectives (3.74); learning activities (3.72); clarity (3.74); accuracy (3.76); appeal (3.67); and usability (3.74). These criteria fall under “strongly agree”. Thus, the developed constructivist learning aid module in disentangling least mastered competencies in wave motion is commendable to use.